Religious Identification and Family Attitudes: An International Comparison - Hayes, Bernadette C. (Research in the social scientific study of religion, 1999)
Using recent cross-national survey data, this study examines the impact of religious identification on attitudes towards the family in seven western societies: the United States, Great Britain, West Germany, the Netherlands, Austria, Italy and Ireland. The results show a marked variation in patterns of religious identification across these countries and significant effects of religious identification on family attitudes. Religious independents are significantly less supportive of marriage, more likely to approve of divorce, and express a less child-centred attitude than both Catholic and Protestant religious affiliates. Thus, for these seven western countries at least, religious identification is a salient predictor of family attitudes.